"Dostig ja vysshei vlasti": Feodor Chaliapin's illness and death - Leonid I. Dvoretsky (LLC "MEDIAFORMAT", 2020)
The article provides data on the nature and course of the disease of F.I. Chaliapin, who suffered from diabetes mellitus with the development of recurrent respiratory infections, severe heart failure. The possibility of developing acute leukemia in the last year of the singer's life is discussed.